Konsep Jiwa dalam al-Qur’an - Sahidi Mustafa (Tasfiyah: Jurnal Pemikiran Islam, 2018)
Basically, Al-Qur’an as Huda (Guidance) has accommodated all of concepts, but the concepts are not mentioned in detail, still in seminal concepts. Moslem scholars have role to derive the seminal concepts to the scientific concepts. At least, al-Qur’an has mentioned 298 times in 270 verses and in 63 chapters. The term of nafs has many meanings according to al-Qur’an, they are, self or someone, self of God, person of something, spirit, soul, totality of human and the inside of human. Human as nafs is not only seen from outside aspect, but also must be seen from inside of it. It is because nafs as a motor of the human behaviors to make changes in life. As motor of behaviors, actually, nafs can move the human to do goodness and badness, according to the quality of nafs it has.